2007
DOI: 10.1016/j.juro.2007.03.190
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Exposure to Benzophenone-2 Causes Hypospadias Through an Estrogen Receptor Dependent Mechanism

Abstract: These findings suggest that benzophenone-2 may cause hypospadias via signaling through the estrogen receptor. Further study of human benzophenone-2 exposure and its effects is needed to support this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…Unfortunately, histopathological examination of the peripheral nerves and muscles around the forelimbs and spinal cord in the thoracic region was not performed in this study. However, no locomotor abnormalities were detected in these groups and similar reduced grip strengths have not been reported in the repeated-dose toxicity studies using benzophenone and related compounds [2,3,5,21,22]. In addition, it has been reported that changes in grip strength are associated with locomotor abnormalities in rats given a number of neurotoxic compounds [23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 68%
“…Unfortunately, histopathological examination of the peripheral nerves and muscles around the forelimbs and spinal cord in the thoracic region was not performed in this study. However, no locomotor abnormalities were detected in these groups and similar reduced grip strengths have not been reported in the repeated-dose toxicity studies using benzophenone and related compounds [2,3,5,21,22]. In addition, it has been reported that changes in grip strength are associated with locomotor abnormalities in rats given a number of neurotoxic compounds [23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 68%
“…For example, BP-2 has been associated with hypospadias in mice (38). The estrogenic effects of BP-2 have been demonstrated in fathead minnows where dose-dependent relationships were observed with gonad histology (testes had fewer spermatocytes), secondary sex characteristics and reproduction (39).…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, BP-2 was shown to have an agonistic effect on fish (rainbow trout) and human ERs, and was found to be selective for human ERβ in an in vitro bioassay (Molina-Molina et al, 2008). BP-2 was also tested in pregnant mice to determine its impact on fetuses, where it was found that BP-2 may be a cause of hypospadia which is an abnormality in the reproductive organs of male fetuses (Hsieh et al, 2007). Additionally, BP-2 suppresses T4 (thyroid hormone), but not T3, and has estrogenic activity in rats (Seidlova-Wuttke et al, 2005).…”
Section: Screening Of Home Products For Estrogenic Activitymentioning
confidence: 99%